Chemical quality of extracted oil and sensory quality of vacuum fried jackfruit (Artocarpus heterophyllus Lam.) pulp as influenced by frying cycle - Braga, Jason D.; Galvez, Lorina A.; Lauzon, Roberta D.; Diczbalis, Yan (Annals of Tropical Research, 2019)
Oil quality is important in the production of quality and safe fried food products. This study aimed to assess the quality of oil extracted from vacuum-fried jackfruit pulp products and the fried products at Visayas State University (VSU), Baybay City, Leyte, Philippines, with the coconut oil used until 20 frying cycles. The percent free fatty acid (FFA), acid value (AV) and peroxide value (PV) of the oil extracted from the product (1st, 5th, 10th, 15th & 20th frying cycle vacuum-fried jackfruit pulp) was determined employing titrimetric method. Quality descriptions and acceptability of the product were obtained through sensory evaluation, following standard protocols. Data were subjected to analysis of variance for significance and post hoc test to compare means. Results revealed that the increase of the frying cycle significantly (p≤0.05) increased the peroxide value, while no significant effect was noted with free fatty acid and acid values. Aroma, taste and general acceptability of the product were significantly affected by the increase in number of frying cycle of oil due to the quality changes of the oil being used. No significant effect was observed for color and texture acceptability with frying cycle. Generally, acceptability of the product decreased with increasing frying cycle. The oil can be recycled at least 10 frying cycles to produce quality and safe vacuum-fried jackfruit product for the consuming public. The reusing of oil provides cost effectiveness in the vacuum-fried jackfruit processing.